LEGAL PROTECTION OF CONSUMERS REGARDING ILLEGAL ONLINE COSMETIC DISTRIBUTION IS REVIEWED FROM LAW NO. 8 OF 1999 CONCERNING CONSUMER PROTECTION - Auchia Indah; Aryuda Aryuda (Jurnal Impresi Indonesia, 2024)
The writing of this scientific paper entitled "Legal Protection of Consumers Regarding the Distribution of Illegal Cosmetics Online given Law no. 8 of 1999 concerning Consumer Protection" aims to find out generally and broadly about cosmetics, why illegal cosmetics can circulate online, the distribution of illegal cosmetics according to applicable law. We need to know what illegal cosmetics mean. Considering the large number of Indonesian women's interest in using beauty products, online business people are flocking to produce their products in various ways, including online marketing. However, on the other hand, due to tight business competition, online business actors act in bad faith by illegally marketing cosmetic products. Just like women, men also use cosmetic products to increase their self-confidence. Many factors cause consumers to use beauty products without knowing the consequences they will get. One of the factors is the need for more consumer education and knowledge regarding illegal cosmetics sold online and sold freely through online sites based on the provisions of the Consumer Protection Law. This research aims to examine and analyze the problem of legal violations for naughty business actors regarding the distribution of cosmetics. This research was carried out normatively, namely library legal research, which refers to consumer legislation. This research focuses on determining legal protection for consumers who use illegal cosmetics sold online. Cosmetics are produced to beautify a person's appearance. However, recently, many cosmetics sold online do not have a circular from BPOM, thus endangering consumers who buy beauty products online.